PENGARUH KEPERCAYAAN, KEAMANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Mutiara; Imam Wibowo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This research analyzes ecommerce on online purchasing decisions. The purpose of this study was to determine the influence of trust, safety, product quality on online purchasing decisions at shopee. The total population used was 1,200 taken from researchers' instagram followers and the number of samples used in this study were 92 respondents. This research is a quantitative study, using simple linear regression analysis and multiple linear regression. The results of this study were obtained simultaneously showing the positive influence of product safety and quality while trust has a negative influence on purchasing decisions. Partially, there is a positive and significant influence of trust, safety and product quality on purchasing decisions. And there is advice given, that shopee companies need to pay attention to consumer confidence and develop the quality of products that are needed and desired by consumers in shopping online.